The Role of a Non-Governmental Organization in the Improvement of Employment in Finland: A Case Study - Thomas Babila Sama; Marja Outi Järvelä (Social Work & Society, 2008)
This study discusses one Non-Governmental Organization (NGO) as an alternative institution for the improvement of employment in a Finnish city. Empirical data was collected from 16 employees and from an official of the organization using questionnaires, interviews and participant observation. The data was analyzed qualitatively and the findings revealed that, the organization plays complementary role in cooperating with the government to provide social services to underprivileged groups of people, through which the organization is able to create jobs for long-term unemployed people in the City of Jyväskylä. However, the skill development training of the organization was found to be inadequate for boosting the employability of their employees in the open labour market, once their 1-2 year contract ended. The study concluded that for the organization to become a viable alternative institution for the improvement of employment in the City of Jyväskylä, it must improve the skill development training of their employees, as well as increase collaboration with other actors that are working towards the same goals.